Development of a neutron tomography system using a low flux reactor - Hungler, P.C.; Bennett, L.G.I.; Lewis, W.J.; Bevan, G.A.; Gabov, A. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2011)
A neutron tomography instrument was designed and developed at the Royal Military College (RMC) of Canada with Queen's University to enhance these institutions' non-destructive evaluation capabilities. The neutron imaging system was built around a Safe Low-Power C(K)ritical Experiment (SLOWPOKE-2) nuclear research reactor. The low power and physical geometry of the reactor required that a novel design be developed to facilitate tomography. A unique rotisserie style rotary stage and clamping apparatus was developed. Furthermore, the low flux at the image plane (3×10 4 n cm −2 s −1), necessitated that the image acquisition and reconstruction processes be optimized. Tomographs of numerous samples were obtained using the new tomography instrument at RMC.